2021
DOI: 10.1111/jocn.15738
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in symptoms and health‐related quality of life as kidney function deteriorates: A cross‐sectional study

Abstract: Aims and objectives To compare symptoms and health‐related quality of life and to examine the relationship between these as kidney function deteriorates. Background Chronic kidney disease is a global health problem, and while knowledge of symptom burden and health‐related quality of life is understood in kidney failure (previously end‐stage kidney disease), there is limited understanding about symptoms and health‐related quality of life across the chronic kidney disease trajectory. Design Cross‐sectional desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…Indeed, chronic kidney disease has a high risk of comorbidity with several neuropsychiatric disorders, such as depression and anxiety disorders, since patients with chronic kidney disease suffer from distress due to continuous various restrictions and long-term medication [28]. Emotional disturbances, such as anxiety or depressive mood/perception can possibly impair and prolong the shared decision-making process, leading to blame being placed on the healthcare team [28,29]. It was previously established that the most important factors for patients when choosing a kidney replacement therapy is their own ability to express their personal values and beliefs based on independence and flexibility [22,30].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, chronic kidney disease has a high risk of comorbidity with several neuropsychiatric disorders, such as depression and anxiety disorders, since patients with chronic kidney disease suffer from distress due to continuous various restrictions and long-term medication [28]. Emotional disturbances, such as anxiety or depressive mood/perception can possibly impair and prolong the shared decision-making process, leading to blame being placed on the healthcare team [28,29]. It was previously established that the most important factors for patients when choosing a kidney replacement therapy is their own ability to express their personal values and beliefs based on independence and flexibility [22,30].…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of studies reported data collected in CKD G4–5 patients (30 studies), whereas far fewer studies reported data on GI symptomatology in the early stages of CKD (6 in G1–2 [ 9 , 32 , 33 , 34 , 35 , 36 ]; 10 in G3 [ 9 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]). Subgroup characteristics were described in Supplementary Materials, Results S1 .…”
Section: Resultsmentioning
confidence: 99%
“…They were conducted primarily in the WHO Western Pacific (9 studies [ 24 , 26 , 35 , 37 , 42 , 55 , 56 , 58 , 64 ]) and European (8 studies [ 23 , 28 , 30 , 31 , 38 , 44 , 53 , 62 , 65 ]) Regions. Data were collected using authors’ questionnaires/during anamnesis in the case of 8 studies, and using validated questionnaires: renal version of the Patient Outcome Scale—symptom module (POS-S Renal; 5 studies [ 24 , 27 , 31 , 35 , 64 ]); Integrated Palliative Care Outcome Scale (IPOS)-Renal (3 studies [ 26 , 37 , 39 ]); Dialysis Symptom Index (DSI) (3 studies [ 23 , 53 , 57 , 58 ]); Memorial Symptom Assessment Scale–Short Form (MSAS-SF; 2 studies [ 44 , 62 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HRQOL can predict disease-related factors and assess prognosis, thus guiding the treatment of specific populations. Poor HRQOL was a common problem in dialysis patients and contributed to low survival rates and high emotional stress ( Yapa et al, 2021 ). With this in mind, HRQOL is increasingly recognized as a key prognostic measure to evaluate the effectiveness of kidney disease treatment ( Lightfoot et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%